ISSUES AND JURISTIC OPINIONS ON THE INVESTMENT OF WAQF FUNDS: AN OVERVIEW FROM THE ENDOWMENT FUND OF KELANTAN ENDOWMENT COMMITTEE - Abdulsoma Thoarlim; Mohammed Muneer’deen O.A.; Asyraf Hj Ab Rahman; Mohamad Zaharuddin Zakaria; Bedjo Santoso (Jurnal Ekonomi dan Bisnis, 2016)
ABSTRACTWakaf is linked to a variety of fields, such as religious, educational, cultural, social and economic.There are several problems and issues facing the Malaysian endowment management as awhole, and Kelantan in particular. Some of the problems and issues are lack of academicallyand administratively qualified personnel in the Wakaf sections/departments, lack of standardsystem for preserving wakaf assets, lack of standard system procedure for the transfer of wakafitems to the Endowment Committee, and so on. There are several contemporary problems andissues surrounding Wakaf management and organization, and the most prevalent of which is theissue of investing Wakaf funds. This is so because it is of great interest to the Malaysian Islamicinstitutions or the Malaysian Islamic council. Based on the importance of the subject, we haveseen the need to examine wakaf applications to Kelantan endowment committee. This studyis comprised of four sections, namely: the emergence of the Kelantan Endowment Committeeand its objectives; the rule of investing endowment funds from the Islamic jurists’ perspective;contemporary decisions on the issue of investing Wakaf funds; and investment of Wakaf fundsin the Kelantan endowment committee. The most important finding of the study is that theKelantan Endowment Commission relates to several fields, as stated by the researchers. It ishoped that the study and its findings will benefit the researchers, the needy ones, as well as theauthorities of Wakaf institutions and committees.Keywords: Investment, Wakaf (Endowment) funds, Endowment committee.